Non‐memory cognitive symptom development in Alzheimer's disease. (29th March 2020) - Blenkinsop, A.; van der Flier, W. M.; Wolk, D.; Lehmann, M.; Howard, R.; Frost, C.; Barnes, J.
Abstract : Background and purpose: Memory is known to be the most common first symptom in Alzheimer's disease (AD). Assessing non‐memory cognitive symptom development in AD is important for understanding disease progression and the potential identification of treatment‐responsive subtypes. Methods: Data from the National Alzheimer's Coordinating Center were examined. Logistic regression models were fitted evaluating the development of judgement, language, visuospatial and attention symptoms at first and second visits to Alzheimer's Disease Centers. Predictors were age and prior symptoms, adjusting for symptom length and sex. The models were then refitted assessing apolipoprotein E ε4 (APOE‐ε4) effects. Results: Each decade reduction in presentation age increased the odds of language, visuospatial and attention symptom development at both visits by 8%–18% ( P < 0.05, all tests), and judgement symptoms at the second visit by 13% ( P < 0.05). Prior symptoms were not equally predictive of symptom development. For example, having first predominant language symptoms carried the lowest risk of developing other first‐visit symptoms and having memory symptoms was a stronger predictor of developing judgement than other symptoms. The APOE‐ε4 gene showed little impact on symptom development when included as a predictor. Conclusions: Our findings provide support for the concept that younger‐onset AD is associated with the progressive development of more non‐memory symptoms beyond the first time point. Associations between symptoms were evident, which may reflect that pathology can remain isolated in a network for some time. APOE‐ε4 status had little influence on cognitive symptom development which may indicate that the effect it has occurs very early in the disease course.